Workplace mobbing and effects on workers’ health - Meseguer de Pedro, Mariano; Soler Sánchez, María Isabel; Sáez Navarro, María Concepción; García Izquierdo, Mariano (The Spanish Journal of Psychology, 2008)
In this work, we analyze various consequences of the phenomenon of mobbing on the health of a work sector with special characteristics: the agro fruit sector. For this purpose, we collected data from a sample of 396 workers (61 men and 331 women) belonging to this sector in the Region of Murcia (Spain). A questionnaire with the following measurement instruments was administered: a Spanish adaptation of the revised Negative Acts Questionnaire (Sáez, García, & Llor, 2003), the Psychosomatic Problems Questionnaire (Hock, 1988), and a measure of absenteeism. The results revealed a significant and positive relation between workplace mobbing and psychosomatic symptoms, but not with absenteeism. The implications of the results for future research are discussed.